Multi-Decadal Humpback Whale Migratory Route Fidelity Despite Oceanographic and Geomagnetic Change - Horton, Travis W.; Zerbini, Alexandre N.; Andriolo, Artur; Danilewicz, Daniel; Sucunza, Federico (Frontiers in Marine Science, 2020)
Understanding how organisms respond to environmental change is one of the most pressing grand challenges of organismal biology. In the vast oceans that cover 71% of Earth’s surface, remote sensing technologies have created unprecedented opportunities to create new knowledge and deliver integrated understandings of marine organism-environment interactions via long-term monitoring. Using historic whaling records and >15 years of satellite-derived data, we show that movement parameters associated with long-distance humpback whale migrations, including utilization of a south-southeast directed migratory corridor, migration path straightness, direction, timing and velocity, have not significantly changed during a period of dynamic oceanographic and geomagnetic conditions. These findings reveal an apparent paradox: humpback whale migrations do not change in a changing ocean. Geophysical analyses of the same humpback whale movements demonstrate that these whales maintained prolonged migratory fidelity to a limited suite of spatiotemporal trajectories through gravitational coordinates, raising the possibility that migratory decisions are relatively insensitive to changing oceanographic and geomagnetic conditions. Our findings highlight the importance of filling the knowledge-gaps that currently limit our ability to understand and anticipate organismal responses to rapidly changing Earth system conditions.